802.11 Security - Fleck, Bob; Potter, Bruce (O'Reilly Media, Incorporated, 2002)
Mention wireless networks, and the question of security will soon follow. It's not surprising that in spite of compelling business arguments for going wireless, many companies are holding back because of security concerns. But, while it's true that wireless networks create security issues that don't exist in wired networks, the issues are not insurmountable. 802.11 Security shows how you can plan for and successfully contend with security obstacles in your wireless deployment. This authoritative book not only explains the security issues, but shows you how to design and build a your own secure wireless network. 802.11 Security covers the entire process of building secure 802.11-based wireless networks, in particular, the 802.11b ("Wi-Fi") specification. The authors provide detailed coverage of security issues unique to wireless networking, such as Wireless Access Points (WAP), bandwidth stealing, and the problematic Wired Equivalent Privacy component of 802.11. You'll learn how to configure a wireless client and to set up a WAP using either Linux or Free BSD. You'll also find thorough information on controlling network access and encrypting client traffic. Beginning with an introduction to 802.11b in general, the book gives you a broad basis in theory and practice of wireless security, dispelling some of the myths along the way. In doing so, they provide you with the technical grounding required to think about how the rest of the book applies to your specific needs and situations. Next, the book details the technical setup instructions needed for both the Linux and FreeBSD operating systems. Some of the topics covered include: Station Security for Linux, FreeBSD, Open BSD, Mac OS X and Windows Setting Up Access Point Security Gateway Security, including building Gateways, firewall Rules, Auditing, et cetera Authentication and Encryption FreeBSD IPsec client and gateway configuration Linux IPsec client and gateway configuration 802.1x authentication 802.11 Security is a book whose time has come. If you are a network, security, or systems engineer, or anyone interested in deploying 802.11b-based systems, you'll want this book beside you every step of the way.